2015
DOI: 10.1094/pdis-12-14-1257-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Boscalid Resistant Botrytis cinerea Isolates Carrying the Mutations H272R, H272Y, P225L, and P225H from Table Grape in Chile

Abstract: Artículo de publicación ISISin acceso a texto complet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Esterio et al (2015) reported the detection of the H272R/Y/L and P255L/H point mutations in table grapes at frequencies of 52.8%, 35.42%, 2.1%, 6.25% and 4.16%, respectively. The introduction of new SDHI fungicides in Chile, such as fluopyram, may modify the structure of local B. cinerea populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esterio et al (2015) reported the detection of the H272R/Y/L and P255L/H point mutations in table grapes at frequencies of 52.8%, 35.42%, 2.1%, 6.25% and 4.16%, respectively. The introduction of new SDHI fungicides in Chile, such as fluopyram, may modify the structure of local B. cinerea populations.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, pyrimethanil, azoxystrobin, boscalid, fenhexamid and fludioxonil fungicides have been used extensively to control gray mold disease in table grapes in Chile, and fungicide resistance of B. cinerea has been reported (Esterio et al, 2007(Esterio et al, , 2012(Esterio et al, , 2015Latorre et al, 2002;Piqueras et al, 2014). We hypothesized that the frequency of multiple-resistance in B. cinerea populations would increase; thus, it would be crucial to monitor such frequency in table grape orchards to evaluate the risk of infection for specific areas and growing conditions and elaborate appropriate anti-resistance strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, fungicides are the most common control method for these pathogens [10]; indeed, table grape and wine sectors represent 50% of the total market value for fungicides [10]. However, fungicide resistance is a growing problem [11][12][13][14][15]. Botrytis management's overall expenses, including cultural measures, botrycides, broad-spectrum fungicides, and biocontrols, easily reach €1 billion/year in all countries; product and quality loss in the market chain, however, is probably much higher [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other mutations such as H272Y or N230I were found in lower frequencies, while P225H was detected in a very low frequency in the population originating from stone fruit rootstock seedlings. P225H mutation is a rather rare mutation that, till now, has been reported only in B. cinerea originating from stone fruit rootstock seedlings in Greece (Konstantinou et al, 2014) and from table grapes in Chile (Esterio et al, 2015). In most of the monitoring studies published previously these mutations are rare or in lower frequencies compared to the frequency of H272R mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of the four sdh subunits in SDHI-resistant strains revealed that resistance was associated with nine target site mutations located in the sdh B subunit and one mutation in the sdh D subunit. In the sdh B subunit mutations associated with resistance to SDHIs have been detected at codons 225, 230, and 272 (Leroux et al, 2010; Veloukas et al, 2011; De Miccolis Angelini et al, 2014a; Esterio et al, 2015). At codon 225 the proline can be substituted by phenylalanine (P225F), leucine (P225L), threonine (P225T), or histidine (P225H).…”
Section: Introductionmentioning
confidence: 99%